Korelasi Hasil Belajar Solfegio Terhadap Hasil Belajar Vokal 1 Mahasiswa Jurusan Sendratasik FBS-UNP - Tirto Agung Pratama; Jagar Lumban Toruan; Yos Sudarman (SENDRATASIK UNP, 2015)
Abstract The purpose of this research was to reveal and explain the correction between the students learning achievement in Solfegio subject and their learning achievement in Vocal class at Sendratasik department of Faculty Language and Art in State University of Padang (FBS-UNP). This was a quantitative research which applied correlation method. Based on the result of coefficient test, it was figured out that the value of r xy was 0,222 on the degree of freedom α 0,05 and the reliability level 95% for which the value of r table was 0,329. After statistic inferential test was done, it was found that the value of r calculated was smaller than r table indicating that the was a low an insignificant correlation the students learning achievement in Solfegio subject and their learning achievement in Vocal class. Hence, Ha was rejected and Ho was accepted. Keyword: Correlation, Learning achievement, Solfegio, Vocal.